Indução de calos e embriogênese em anteras de Coffea arabica L. - Silva, Adelaide Siqueira (2007)
Coffee breeding through convention methods, especially hybridization, followed by population selection, progeny evaluation, back-crossings and inter-specific crossings is a time consuming process that can demand for more than 30 years to obtain a new cultivar. It is possible to reduce this time by producing homozygous lines, from di-haploids, obtained from anther culture. This study applied anther culture technique on different Coffea arabica L. cultivars to induce the formation of calli and regenerate di-haploid germlings. The experiments were done in the Vegetable Biotechnology Laboratory of Universidade Federal de Uberlândia (UFU). Experiment 1: Flower buds of cultivars Mundo Novo LCP-379-19 and Catuaí Vermelho H2077-2-5-44 were collected, disinfested and the anthers were inoculated in MS supplemented with 2.0 mgL-1 de 2,4-D and AAS at de 0.0, 8.0, 16.0, 32.0 or 64.0 mgL-1. Experiment 2: Calli of Catuaí Vermelho 44 were transferred to MS amended with different concentration of BAP (0.0, 2.0, 4.0 or 8.0 mgL-1) and 2,4-D (0.0, 1.0, 2.0 or 4.0 mgL-1). Experiment 3 (1st part): Flower buds of cultivar Catuaí Vermelho 99 were collected, disinfested and the anthers inoculated in MS amended with 2 mgL-1 2,4-D in the absence or presence of 5 mgL-1 silver nitrate together with ETHREL for different days: control (0), 2, 4, 6, or 8 days. (2nd part): After 12 days, the anthers were transferred to a regeneration medium, amended with 0.108 mgL-1 kinetin. A greater anther exposition time to ethylene, or longer inoculation time, favored the oxidation, and the alone ethylene favored formation of calli, Catuaí Vermelho 99 is responsive to intumescence, to calli formation and, also, to direct embryogenesis, in the presence of ethylene; AgNO3 together with ethepon, favored anther intumescence and calli formation; AgNO3 together with 2.0 mg L-1 2,4-D, promoted direct embryogenesis, for Catuaí Vermelho 44, the treatment with 2.0 mgL-1 2,4-D and 0.0 mgL-1 AAS was the one that presented the greatest average of calli formation; for both Mundo Novo and Catuaí Vermelho 44 the increase in AAS concentration decreased the pro-embryo formation in the calli; auxin, by itself, was capable of promoting the formation of friable calli, however the balance of the auxin and the BAP used in the work, had favored the production of friable calli.